2002
DOI: 10.1109/tpwrs.2002.804998
|View full text |Cite
|
Sign up to set email alerts
|

An improved branch-exchange algorithm for large-scale distribution network planning

Abstract: Design of optimal layout for medium-voltage power networks is a common issue in electrical distribution planning. Technical constraints (radial structure, voltage drops, and equipment capacity), and reliability limits must be fulfilled. The function for minimizing includes investments, power losses, and quality of supply costs. We present in this paper an improved algorithm based on a branch-exchange technique to solve large-scale problems. A heuristic algorithm for solving a Euclidean Steiner problem is used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
47
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(52 citation statements)
references
References 13 publications
0
47
0
5
Order By: Relevance
“…Actually they do not use any optimisation algorithm, but try to find a good solution by a technical strategy. Branch exchange approach is the most common technical strategy which has been applied to distribution system optimisation problem [27][28][29][30][31][32][33]. The third category of approaches is metaheuristics which are very popular in solving distribution system optimisation problems and have shown satisfactory performance [34][35][36][37].…”
Section: Review From Viewpoint Of Used Optimisation Algorithms Objecmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually they do not use any optimisation algorithm, but try to find a good solution by a technical strategy. Branch exchange approach is the most common technical strategy which has been applied to distribution system optimisation problem [27][28][29][30][31][32][33]. The third category of approaches is metaheuristics which are very popular in solving distribution system optimisation problems and have shown satisfactory performance [34][35][36][37].…”
Section: Review From Viewpoint Of Used Optimisation Algorithms Objecmentioning
confidence: 99%
“…For example, in [135], modified ant colony optimisation, in [136], simulated annealing, in [137], modified differential evolution (DE) with changing scaling factor, in [138], fuzzy DE, in [139], chaotic DE, in [27][28][29][30][31][32][33], branch exchange method (a technical approach), in [140], an expert system based on some heuristic rules and in [141], a greedy search algorithm have been applied to distribution system optimisation problem. Table 1 presents the classification of existing research works on distribution system optimisation problem from the viewpoint of used optimisation algorithms, used objectives and used decision vectors.…”
Section: Review From Viewpoint Of Used Optimisation Algorithms Objecmentioning
confidence: 99%
“…Three-dimensional problems are also of practical concern. Such problems emerge in VLSI chip layout design, distribution network planning [6], wireless and sensor networks [7], robotics and molecular structure modeling [8]. A good review of Steiner tree applications can be found in [7], robotics and molecular structures modeling [8].…”
Section: Introductionmentioning
confidence: 99%
“…Tradicionalmente, los estudios de planeamiento en distribución se han basado en la ampliación de la capacidad de las subestaciones, la instalación de nuevas subestaciones, el refuerzo o construcción de nuevas líneas y la recon¿ guración de redes [3]- [4]. No obstante, en la última década se han reportado numerosos trabajos que incluyen la ubicación de nuevas unidades de GD como una alternativa dentro de los estudios de planeamiento de redes de distribución.…”
Section: Introductionunclassified